Kiai dan Tradisi Penulisan Manuskrip Mushaf sebagai Wujud Dialektika Agama dan Budaya - zakiyatul Anisah; Abd Warits; Abdul Wahid; Fathurrosyid Fathurrosyid (JSP: Jurnal Studi Pesantren, 2023)
Quranic mushaf manuscripts constitute cultural heritage rich in historical, theological, and cultural information, yet public understanding of their significance remains limited. This research aims to analyze the relationship between kiai (Islamic scholars) and the tradition of mushaf manuscript writing in Sumenep Madura, as well as examine the dialectic between religion and culture by positioning kiai as cultural mediators. The study employs a qualitative approach through participatory observation, in-depth interviews, and documentation analysis of mushaf manuscripts from kiai collections and Sumenep community. Hiroko Horikoshi's cultural mediator theory is utilized to analyze the role of kiai in responding to and shaping cultural practices related to mushaf manuscripts. Research findings indicate that the examined manuscripts belong to the 18th and 19th-century categories with distinctive characteristics in paleography, ornamentation, and writing techniques. The religion-culture dialectic manifests in five cultural practices: the tradition of khatam Al-Qur'an (Quranic completion ceremonies), Quranic teaching, the use of the Qur'an as amulets, application of fragrance to mushaf, and beliefs in the mystical value of the Qur'an. Kiai function as cultural mediators who legitimate these practices through theological reinterpretation that accommodates local beliefs without contradicting Islamic teachings. This research reveals that the religious authority of kiai serves as a determining factor in negotiating between Islamic orthodoxy and Madurese local traditions